Progression of Aortic Arch Calcification Is Associated with Overall and Cardiovascular Mortality in Hemodialysis - Chung, Wei-Shiuan (Dis Markers, 2020)
BACKGROUND: Vascular calcification is common and associated with unfavorable outcomes among patients with end-stage renal disease (ESRD). Nevertheless, little is known whether the progression of vascular calcification outweighs the baseline calcification in association with overall and cardiovascular (CV) mortality in hemodialysis (HD) patients. METHODS: This study included 140 maintenance HD patients. Vascular calcification was assessed using the aortic arch calcification (AoAC) score measured from chest radiographs at the baseline and the second year of follow-up. Progression of vascular calcification (ΔAoAC) was defined as the difference between the two measurements of AoAC. The association of ΔAoAC with overall and CV mortality was evaluated using multivariate Cox regression analysis. RESULTS: During the mean follow-up period of 5.8 years, there were 49 (35%) overall mortality and 27 (19.3%) CV mortality. High brachial-ankle pulse wave velocity was positively correlated with ΔAoAC, whereas old age was negatively correlated with ΔAoAC. In multivariate adjusted Cox analysis, increased ΔAoAC (per 1 unit), but not baseline AoAC, was significantly associated with overall mortality (HR, 1.183; 95% CI, 1.056–1.327; p = 0.004) and CV mortality (HR, 1.194; 95% CI, 1.019–1.398; p = 0.028). CONCLUSION: Progression of AoAC outperformed the baseline AoAC in association with increased risk of overall and CV mortality in HD patients. A regular follow-up of chest radiograph and AoAC score assessments are simple and cost-effective to identify the high-risk individuals of unfavorable outcomes in maintenance HD patients.